2020
DOI: 10.21037/atm-20-3805
|View full text |Cite
|
Sign up to set email alerts
|

Minimum local anesthetic dose of ropivacaine in real-time ultrasound-guided intraspinal anesthesia for lower extremity surgery: a randomized controlled trial

Abstract: Background: Despite the many advantages real-time ultrasound-guided lumbar anesthesia has over traditional lumbar anesthesia, it seemingly involves a much higher dose of ropivacaine. This study aimed to determine the minimum local anesthetic dose (MLAD) and the 95% confidence interval of ropivacaine at different concentrations in real-time ultrasound-guided lumbar anesthesia for lower extremity surgery.Methods: A total of 60 patients who were consecutively scheduled for selective lower extremity surgery were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In addition, due to slow drug metabolism, patients are prone to delayed awakening or even temporary brain dysfunction after surgery, which increases the risk of complications and affects the patient's rehabilitation (16,17). Previous studies have found that intraspinal anesthesia has the characteristics of good analgesic effect, small drug consumption, and the block range is limited to one side, which can effectively reduce the sympathetic activity and reduce vasodilation, thereby reducing the damage to the circulatory system and the occurrence of adverse events, and effectively meeting the basic needs of hip replacement in the elderly (18,19). Our patient avoided endotracheal intubation and mechanical ventilation with relatively low respiratory complications; The incidence of nausea and vomiting is low; Epidural analgesia can be performed with good postoperative analgesic effect.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, due to slow drug metabolism, patients are prone to delayed awakening or even temporary brain dysfunction after surgery, which increases the risk of complications and affects the patient's rehabilitation (16,17). Previous studies have found that intraspinal anesthesia has the characteristics of good analgesic effect, small drug consumption, and the block range is limited to one side, which can effectively reduce the sympathetic activity and reduce vasodilation, thereby reducing the damage to the circulatory system and the occurrence of adverse events, and effectively meeting the basic needs of hip replacement in the elderly (18,19). Our patient avoided endotracheal intubation and mechanical ventilation with relatively low respiratory complications; The incidence of nausea and vomiting is low; Epidural analgesia can be performed with good postoperative analgesic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Intraspinal anesthesia (lumbar spinal nerve anesthesia) is a kind of local anesthesia, which is currently very common in clinic. According to the different injection positions, it can be divided into epidural anesthesia, combined spinal epidural anesthesia, and subarachnoid anesthesia (also known as spinal anesthesia/lumbar anesthesia) [ 1 – 3 ]. Lumbar spinal nerve anesthesia is widely used in cesarean section, lower limb surgery, hemorrhoidectomy, and the supplementary treatment of cardiovascular diseases [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…More patients develop bradycardia and need the sympathomimetic drug 4 . The newly introduced drug, i.e., ropivacaine, has a more specific effect on the motor nerve fibers [5][6][7] . Furthermore, this drug has lesser cardiac toxicity 8 .…”
Section: Introductionmentioning
confidence: 99%